Answer:
37 and 29
Step-by-step explanation:
x + y = 66
x - y = 8
*******************************************
solve second equation for x
x = y + 8
substitute for x in first equation
y+8 +y = 66
2y = 58
y = 29
*******************************************
x - 29 = 8
x = 37
******************************************
x = 37 and y = 29
Final answer:
To solve for the two numbers, set up equations based on the sum and difference provided. By solving these equations, we find that the numbers are 52 and 14.
Explanation:
The sum of two numbers is 66, and their difference is 38. This problem can be solved using a system of equations. Let's denote the two numbers as x and y.
According to the information given:
x + y = 66 (Equation 1)x - y = 38 (Equation 2)Now, we can solve these equations simultaneously.
Add Equation 1 and Equation 2: (x + y) + (x - y) = 66 + 38, which simplifies to 2x = 104. Therefore, x = 52.Substitute x = 52 into Equation 1: 52 + y = 66, so y = 66 - 52, which gives us y = 14.The two numbers that satisfy the conditions of the problem are 52 and 14.
Amit built a sand castle that measured 600 centimeters by 600 centimeters, and dug a moat around it.
Afterward, he decided to change the castle size, making it 8 meters by 6 meters.
How much longer will the new moat be than the old one?
Answer:
4 meters longer.
Step-by-step explanation:
Amit built a sandcastle that measured 600 cm by 600 cm i.e. 6 meters by 6 meters.
Therefore, its perimeter is 2(6 + 6) = 24 meters
Now, afterward, he decided to change the castle size, making it 8 meters by 6 meters.
Therefore, its perimeter is 2(6 + 8) = 28 meters
Therefore, the perimeter of the new castle is increased by (28 - 24) = 4 meters.
If Amit dug a moat around his castle then the new moat will be 4 meters longer than the old one. (Answer)
As the moat is dug around the castle, its length will be the same as the perimeter of the castle.
A restaurant manager can spend at most $400 a day for operating costs and payroll. It costs $100 each day to operate the bank and $50 dollars a day for each employee. Use the following inequality to determine how many employees the manager can afford for the day, at most: 50x + 100 ≤ 600
Answer:
The restaurant Manager can afford 6 employees for the day.
Step-by-step explanation:
Manager can spend at most of $400.
Total Money ≤ $400
Cost to operate bank = $100
Cost for each employee = $50
Let number of employees for the day be[tex]x[/tex]
Hence the equation will become;
[tex]50x + 100 \leq 400[/tex]
Solving this equation we get;
[tex]50x + 100 \leq 400\\50x \leq 400-100\\50x \leq 300\\x\leq \frac{300}{50}\\\\x\leq 6[/tex]
Hence, The restaurant Manager can afford 6 employees for the day.
Answer:
x < = 10
Step-by-step explanation:
i did it on photo math so yah
What is 8.4 x 10^12/4.2 x 10^6
Answer:
2 × [tex]10^{6}[/tex]
Step-by-step explanation:
Using the rule of exponents
[tex]\frac{a^{m} }{a^{n} }[/tex] ⇔ [tex]a^{(m-n)}[/tex]
Split the fraction into a product, that is
= [tex]\frac{8.4}{4.2}[/tex] × [tex]\frac{10^{12} }{10^{6} }[/tex]
= 2 × [tex]10^{(12-6)}[/tex]
= 2 × [tex]10^{6}[/tex]
If lines m and n are parallel, and the measure of
angle 1 is 130°, what is the measure of angle 8?
Answer:
18.55, lines m and n are parallel and t is the transversal. If ∠1 = 130o, find the measures of the other angles and give reasons.
Step-by-step explanation:
The measure of angle 8 will be 130° since it corresponds to angle 1, and their measures are equal because lines m and n are parallel.
Explanation:To find the measure of angle 8 when lines m and n are parallel, and the measure of angle 1 is 130°, it's important to understand the concept of corresponding angles in the context of parallel lines. Corresponding angles are equal when two lines are parallel. Given that angle 1 is 130°, and assuming that angle 1 and angle 8 are corresponding angles (since the question does not specify their positions), the measure of angle 8 is also 130°.
Learn more about Parallel Lines and Angles here:https://brainly.com/question/17237586
#SPJ2
There's 5 trees fill with apples. Alex wants 2 off each tree. How much apples do she have?
Answer:
10
Step-by-step explanation:
5 trees * 2 from each = 10 apples
Answer:
10
Step-by-step explanation:
5*2=10
8/11 divide by 3/5
find the quotient
Answer:
=40/33
8/11 divide 3/5 -> 8/11 x 5/3 and multiply 8x5 then 11x3 then u got your answer! :)
Hope this worked :D
Answer:
Your answer is 40/33
Step-by-step explanation:
8/11 * 3/5
flip the fraction
8/11* 5/3
Multiply
Please help me I need help quick
!!!!
Jim’s new car has 150 miles on the odometer. He takes a trip and drives an average of m miles each day for three weeks. Which expression represents the mileage on Jim’s car after his trip?
Answer:
[tex](150+21m)\ miles[/tex]
Step-by-step explanation:
we know that
[tex]1\ week=7\ days[/tex]
Remember that the speed is equal to divide the distance by the time
Let
s ---> the speed in miles per day
d ---> the distance in miles
t ---> the time in days
[tex]s=\frac{d}{t}[/tex]
[tex]d=st[/tex]
we have
[tex]s=m\ miles/day[/tex]
[tex]t=3\ weeks[/tex]
Convert to days
[tex]t=3(7)=21\ days[/tex]
Find the distance covered in the trip
[tex]d=st[/tex] ----> [tex]d=m(21)=21m\ miles[/tex]
To find out the mileage on Jim’s car after his trip, sum the mileage before his trip (150 miles) plus the mileage of the trip
[tex](150+21m)\ miles[/tex]
need help please and thanks
Answer:
2. n = 11
4. g = -2
6. t = 21
8. n = 4
10. y = -1
Step-by-step explanation:
2. 63 = -3(1 - 2n)
Dividing both the side by negative 3 we get
[tex]-21=1-2n\\2n=1+21\\2n=22\\n=\frac{22}{2} \\\therefore n=11[/tex]
4. -g + 2(3 + g) = -4(g + 1)
First we will open the bracket by distributive property A( B +C) = AB + AC
[tex]-g+2\times 3 + 2\times g = -4\times g + -4\times 1\\-g+6+ 2g=-4g-4\\\textrm{we will take all the g term the left side and the constant to the right side}\\4g-g+2g=-6-4\\5g=-10\\g=\frac{-10}{5}\\\therefore g=-2[/tex]
6.-3(t +5 ) + (4t + 2) = 8
Using distributive property A( B +C) = AB + AC we get
[tex]-3\times t + -3\times 5 + 4t + 2=8\\-3t-15+ 4t + 2=8\\t=8+15-2\\t=21\\\therefore t=21\\[/tex]
8. -8 - n = -3(2n -4)
Using distributive property A( B +C) = AB + AC we get
[tex]-8 - n = -3\times 2n - -3\times4\\-8-n=-6n+12\\\textrm{all the n terms to the left inside and the constant of the right-hand side}\\6n-n=8+12\\5n=20\\n=\frac{20}{5}\\ \therefore n= 4[/tex]
10. -4( 2 - y) + 3y = 3(y - 4)
Using distributive property A( B +C) = AB + AC we get
[tex]-4\times 2 --4\times y + 3y = 3\times y -3\times 4\\-8+4y+3y =3y-12\\\textrm{all the y terms to the left side and the constant to the right side}\\4y+3y-3y=-12+8\\4y=-4\\y=\frac{-4}{4}\\ \therefore y=-1[/tex]
Help me please with question 4 b
Answer:
see explanation
Step-by-step explanation:
The second term of sequence P is 2a + b
The third term of sequence Q is 3b + a
Equating gives
2a + b = 3b + a ( subtract a from both sides )
a + b = 3b ( subtract b from both sides )
a = 2b ← as required
Good evening ,
Step-by-step explanation:
4 (b)
The 2nd term of sequence P is 2a+b
The 3rd term of sequence Q is 3b+a
2a+b=3b+a ⇌ (2a-a) = (3b-b) ⇌ a=2b.
:)
Find the value of each expression.
10. |-41|
12. -|1.5|
Step-by-step explanation:
10. |-41|= 41
12. -|1.5|= -1.5
Answer:
A.) 41
B.) -1.5
Step-by-step explanation:
Absolute value means to make whatever that is inside positive
10.) The absolute value of negative 41 would simply be positive 41
11.) Since the negative sign is on the outside of the absolute value, you do the absolute value of everything inside then apply a negative sign. Absolute value of 1.5 is just 1.5 because it's already positive. Then apply the negative sign, which would make it -1.5
What is the final step in solving the inequality -2(5 - 4x)
Step 1: -10 + 8x < 6x - 4
Step 2: -10 <-2x - 4
Step 3: -6<-2x
Step 4
AVA
Step-by-step explanation:
[tex]-2(5-4x)<6x-4\qquad\text{use the distributive property}\\\\(-2)(5)+(-2)(-4x)<6x-4\\\\-10+8x<6x-4\qquad\text{subtract}\ 8x\ \text{from both sides}\\\\-10+8x-8x<6x-8x-4\\\\-10<-2x-4\qquad\text{add 4 to both sides}\\\\-10+4<-2x-4+4\\\\-6<-2x\qquad\text{divide both sides by (-2)}\\_{\text{by dividing by a negative number, flip the inequality sign}}\\\\3>x[/tex]
. In an encyclopedia of language, the author presents five sentences that make a reasonable paragraph regardless of their order. The sentences are listed below. Mark had told him about the foxes. John looked out of the window. Could it be a fox? However, nobody had seen one for months. He thought he saw a shape in the bushes. In how many different orders can the five sentences be arranged?
Answer:
the 1st & last paras are fixed.
that leaves 3 to be put in any order
there are 3 choices for the 1st,
2 choices left for the 2nd
and just 1 choice for the last
multiply to get
3*2*1
= 6 ways
We want to find the total number of orders in which we can order the given sentences.
We will see that there are 120 different orders.
There are 5 sentences, let's define them as:
s₁ = Mark had told him about the foxes.s₂ = John looked out of the window.s₃ = Could it be a fox? s₄ = However, nobody had seen one for months.s₅ = He thought he saw a shape in the bushes.We know that we can order these in any order, so we can think of the situation as 5 empty slots, in each slot, we can put one of the previous statements.
Let's count the number of options for each one of these slots.
On the first one, we have 5 options (5 sentences)
On the second one we have 4, because we already used one on the first slot.
On the third, we have 3 options.
On the fourth, we have 2 options.
On the fifth, we have 1 option.
The total number of combinations is given by the product of these numbers of options.
Combinations = 5*4*3*2*1 = 120
If you want to learn more, you can read:
https://brainly.com/question/3732964
3х – 2 y = 0
I need some help idk why but I just can’t remember how to do this one
Answer:
y=3x/2
Step-by-step explanation:
first you want to get the -2y alone so you move the 3x. since it's adding now the opposite of addition is subtraction. now your left with -2y= -3x. since your trying to solve for y now you divide -2 on both sides and your gonna be left with y= -3x/-2. since their both negatives it turns to postive. that's why the answer would be y= 3x/2.
Step-by-step explanation:
this line will cross the origin
to help I'm just going to explain something real quick.
make it into y intercept form (y=mx+b)
-2y=0-3x
y=3/2x +0
the m (3/2) is the slope
and b (0) is the y intercept
if you want to check it then imput a point on the line into the x and y variables
14) What is the graph of the function rule ?
y= |2x|-1
Because the equation contains an absolute value, the shape of the graph would be a V,.
The Y intercept is -1, so this would be the lowest point on the graph.
Replace X with 1 and solve:
y = 2(1) -1 = 2-1 = 1, so another point would be (1,1) and another point would be (-1,1) ( Absolute value would use both -1 and 1 as the same).
Make 3 points on the graph:
(-1,1) (1,1) ans (0,-1) and draw lines through them.
See attached picture:
Simultaneous equations !
Who can help
The cost of glass is: £4
The cost of mug = £2
Step-by-step explanation:
Let g be the number of glasses and
m be the number of mugs
[tex]3g+3m = 18\ \ \ \ \ Eqn\ 1\\6g+4m=32\ \ \ \ \ Eqn\ 2[/tex]
Multiplying equation 1 by 2
[tex]6g+6m=36\ \ \ \ Eqn\ 3[/tex]
Subtracting Eqn 2 from Eqn 3
[tex]6g+6m - (6g+4m) = 36-32\\6g+6m-6g-4m=4\\2m=4[/tex]
Dividing both sides by 2
[tex]\frac{2m}{2} = \frac{4}{2}\\m = 2[/tex]
Putting m=2 in eqn 1
[tex]3g+3(2) = 18\\3g+6 = 18\\3g = 18-6\\3g = 12[/tex]
Dividing both sides by 3
[tex]\frac{3g}{3} = \frac{12}{3}\\g = 4[/tex]
Hence,
The cost of glass is: £4
The cost of mug = £2
Keywords: Linear Equation, simultaneous equations
Learn more about linear equation at:
brainly.com/question/2367554brainly.com/question/2670657#LearnwithBrainly
A park ranger at the top of a 700-meter station sees a fair that is 1800 meters from the base of the tower.
What is the angle of elevation in degrees?
Final answer:
To find the angle of elevation, we can use the concept of tangent. The angle of elevation is approximately 67.7 degrees.
Explanation:
To find the angle of elevation, we can use the concept of tangent.
Tan(Angel of Elevation) = Opposite/Adjacent
Here, the opposite side is the height of the fair, which is 1800 meters, and the adjacent side is the height of the station, which is 700 meters.
Tan(Angel of Elevation) = 1800/700
Angel of Elevation = tan-1(1800/700)
Using a calculator, the angle of elevation is approximately 67.7 degrees.
For apples 2 lb for $3.38 unite rate___ cost___
Answer:
1.69
Step-by-step explanation:
well to find out the unit rate that would be a pound now we need to find out how much it would cost for 1 lb which would be 3.38 / 2 which would be 1.69 as your answer
Answer:
$1.69 per pound
Step-by-step explanation:
3.38/2=1.69
how do you make 1 1-2/1-6-7/8 a mixed number
Answer:
17/8
Step-by-step explanation:
2/1=2
11-2-6-7/8
9-6-7/8
3-7/8
24/8-7/8
17/8
The black graph is the graph of y=f(x). Choose the equation for the red graph.
Please help!!!
Answer:
C
Step-by-step explanation:
Given f(x) then f(x) + c is a vertical translation of f(x) by c units
• If c > 0 then shift c units up
• If c < 0 then shift c units down
The red graph is a vertical translation f(x) of 3 units down
Thus
y = f(x) - 3 ( add 3 to both sides )
y + 3 = f(x) ← equation of red graph
If 6 + 2 = 8, does 6+2 +3= 8+3? Why or
why not?
Answer:
yes
Step-by-step explanation:
Because 6+ 2 equals 8 then plus 3 equals 11 and 11 equals 8+3
Please help solve with steps: Order of operation with integers.
6 (divide by ) (-3) - (-9)
Answer:
7Step-by-step explanation:
Use PEMDAS:
P Parentheses first
E Exponents
MD Multiplication and Division
AS Addition and Subtraction
[tex]6:(-3)-(-9)[/tex] first - division
[tex]=-2+9[/tex] use commutative property a + b = b + a
[tex]=9+(-2)=9-2=7[/tex]
The first three terms of a geometric sequence are as follows.
-4, -12, -36
Find the next two terms of this sequence.
Give exact values (not decimal approximations).
-4, -12, -36, 1:0
:
:
x
5
Answer:
The next two terms for the geometric sequence are - 108 and - 324.
Step-by-step explanation:
1. Let's find the next two terms for the geometric sequence which first three terms are as follows:
- 4, 12, - 36.....
Aₓ = Aₓ₋₁ * 3 ; A₁ = - 4
A₁ = - 4
A₂ = A₁ * 3 = - 4 * 3 = - 12
A₃ = A₂ * 3 = - 12 * 3 = - 36
A₄ = A₃ * 3 = - 36 * 3 = - 108
A₅ = A₄ * 3 = - 108 * 3 = - 324
The next two terms for the geometric sequence are - 108 and - 324.
Determine the next three terms in the following sequence:
1, 2, 5, 10,
a 17, 26, 37
b. 19, 30, 43
c50, 500, 25,000
d. 15, 25, 40
The correct sequence is a. 17, 26, 37.
To determine the next three terms in the sequence, we must first identify the pattern governing the sequence. Let's examine the differences between consecutive terms:
- The difference between the second term (2) and the first term (1) is 1.
- The difference between the third term (5) and the second term (2) is 3.
- The difference between the fourth term (10) and the third term (5) is 5.
- The difference between the fifth term (17) and the fourth term (10) is 7.
We can see that the differences between consecutive terms are increasing by 2 each time. This suggests that the sequence is generated by adding consecutive odd numbers to the previous term. To find the next terms, we continue this pattern:
- The sixth term will be the fifth term (17) plus the next odd number (9), which is 17 + 9 = 26.
- The seventh term will be the sixth term (26) plus the next odd number (11), which is 26 + 11 = 37.
- The eighth term will be the seventh term (37) plus the next odd number (13), which is 37 + 13 = 50.
Therefore, the next three terms of the sequence are 26, 37, and 50, confirming option a as the correct answer.
find the slope and the y-intercept of y=9x-2
Answer:
The Slope is 9 and the y-intercept is -2
Step-by-step explanation:
Answer: slope=9
Y-intercept=-2
Step-by-step explanation:
Use y=mx+b where m equals slope and b equals y-intercept
-2+4(-x+4)=10 using distributive property and collecting like terms
Answer:
x = 1Step-by-step explanation:
[tex]-2+4(-x+4)=10\qquad\text{use the distributive property:}\ a(b+c)=ab+ac\\\\-2+(4)(-x)+(4)(4)=10\\\\-2-4x+16=10\qquad\text{combine like terms}\\\\-4x+(-2+16)=10\\\\-4x+14=10\qquad\text{subtract 14 from both sides}\\\\-4x+14-14=10-14\\\\-4x=-4\qquad\text{divide both sides by (-4)}\\\\\dfrac{-4x}{-4}=\dfrac{-4}{-4}\\\\x=1[/tex]
The graphs below have the same shape. What is the equation of the blue graph?
Answer:
Option C. [tex]g(x)=(x+5)^{2}[/tex]
Step-by-step explanation:
we know that
The equation of the parent function f(x) (red graph) is
[tex]f(x)=x^{2}[/tex]
This is a vertical parabola open upward
The vertex is the point (0,0) (the origin)
The function g(x) (blue graph) is a vertical parabola open upward
The vertex is the point (-5,0)
The transformation of f(x) to g(x) has the following rule
f(x) -----> g(x)
(0,0) ----> (-5,0)
(x,y) ----> (x-5,y)
That means----> The transformation is a translation of 5 units at left
therefore
The equation of g(x) is
[tex]g(x)=(x+5)^{2}[/tex]
Karen bought a coat for 20% more than the price she wanted to pay. If she paid $150, how much was she looking to pay?
The first one to get both correct will be brainiest!!!!!!!
120% = $150
divide both sides by 6
20% = $25
We want the regular price, so 100%.
multiply both sides by 5
100% = $125
Answer:125
Step-by-step explanation:
150/1.20
=125
Formulate the recursive formula for the following geometric sequence.
{-16, 4, -1, ...} Show all your work please:)
The recursive formula for given sequence is:
[tex]a_n = -\frac{1}{4}a_{n-1}[/tex]
Step-by-step explanation:
Given sequence is:
-16, 4, -1, ...
First of all, we have to find the common ratio. common ratio is the ratio between two consecutive terms of a geometric sequence
Here
[tex]a_1 = -16\\a_2 = 4\\a_3 = -1\\Now\\r = \frac{a_2}{a_1} = \frac{4}{-16} = -\frac{1}{4}\\r = \frac{a_3}{a_2} = \frac{-1}{4} = -\frac{1}{4}[/tex]
The recursive of geometric sequence is:
[tex]a_n = r * a_{n-1}[/tex]
Putting the value of r
[tex]a_n = -\frac{1}{4}a_{n-1}[/tex]
Hence,
The recursive formula for given sequence is:
[tex]a_n = -\frac{1}{4}a_{n-1}[/tex]
Keywords: Geometric sequence, Recursive formula
Learn more about geometric sequence at:
brainly.com/question/11286417brainly.com/question/12884373#LearnwithBrainly
2. Use the linear combination method to solve the system of equations. Explain each step of your solution
3x - By = 7
x +2y = -7
x = - 3
y = -2
Step-by-step explanation:
3x - 8y = 7
x +2y = -7
We standardize the coefficient of one variable such that it addition will result to zero;
3x - 8y = 7
(x +2y = -7)4
Then multiply the one equation with a constant (this case 4) to get;
3x – 8y = 7
4x + 8y = - 28
We add the two equations;
3x – 8y = 7
+
4x + 8y = - 28
=
7x = - 21
x = -21 / 7
x = - 3
Now we evaluate y by replacing the value of x with -4 in one of the equation;
x +2y = -7
-3 +2y = -7
2y = -7 + 3
2y = - 4
y = -2
Learn More:
For more on linear combination check out;
https://brainly.com/question/13959574
https://brainly.com/question/12057389
#LearnWithBrainly
What is the exact volume of the cone?
108π cm3
162π cm3
18π cm3
486π cm3
V = π·r²·h/3 = π·81·6/3 = 2·81·π = 162π cm³